Relevansi Intelllectual Capital dan Kinerja Keuangan terhadap Harga Saham Perusahaan Perbankan yang Terdaftar di BEI - Valentina, Yunita -; Dahar, Reni -; Mulyani, Fitrah - (Jurnal Kajian Manajemen Bisnis, 2015)
This study aims to present empirical evidence on the relationship of Intellectual Capital and financial performance of the share price on the banking companies listed in Indonesia Stock Exchange 2008-2012. The method of analysis used in this study is a quantitative method with the statistical analysis of linear regression analysis. Results of this study indicate that investors are less expensive aspects of human resources is recognized as a source of comparative advantage of the company, while taking investment decisions in the sample companies. In this study, one of the indications that cause this is the Intellectual Capital is not fully able to increase its profit is the company has not succeeded in managing knowledge so that employees can not increase the value of the company in this case is measured by the share price. Rationalization that can be given to explain this finding that stakeholders are still focused on the ability of management to manage their physical assets.